Evaluation The Effect Of HTGN Treatments On The Corrosion Resistance and Magnetic Properties Of Austenitic Stainless Steel 316L And 316LVM - Suprihanto, Agus (University of Muhammadiyah Malang, 2017)
High temperature gas nitriding (HTGN) is the new methods to enhanced the properties of stainless steel. The HTGN process is able to diffuse the nitrogen atom into stainless steel. Increasing the nitrogen concentration produces higher corrosion resistance. Stainless steel for implant and medical devices such as 316L and 316LVM not only have to high corrosion resistance but also have to magnetic properties stabilities. Evaluation of corrosion and magnetic properties for austenitic stainless steel 316L and 316LVM after HTGN treatments was succesfully done. The corrosion resistance not only significantly increases but the stability of austenite phase is also increases. Therefore HTGN treatments is suitabe for improving the corrosion resistance for 316L and 316LVM which used as implant material.